Handbook of Peer-to-Peer Networking - Shen, Xuemin; Yu, Heather; Buford, John; Akon, Mursalin (Springer US : Imprint: Springer, 2010)
Peer-to-peer networking, a disruptive technology for large scale distributed applications, has gained widespread attention due to the successes of peer-to-peer (P2P) content sharing, media streaming, and telephony applications. In addition, a large range of new applications are under development or being proposed. The underlying architectures share features including decentralization, end system resources, autonomy, virtualization, and self-organization. These features constitute the P2P paradigm. Trends in information and network technology such as increased performance and deployment of broadband networking, wireless networking, and mobile devices are synergistic with and reinforce the capabilities of this P2P paradigm. The Handbook of Peer-to-Peer Networking is dedicated to discussions on P2P networks and their applications, thus providing an exhaustive view of the state-of-the-art of the P2P networking field. Written by leading international experts, the volume contains fifty chapters dedicated to the following topics: • Introduction to Peer-to-Peer Networking • Unstructured P2P Overlay Architectures • Structured P2P Overlay Architectures • Search and Query Processing • Incentive Mechanisms • Trust, Anonymity, and Privacy • Broadcast and Multicast Services • Multimedia Content Delivery • Mobile P2P • Fault Tolerance in P2P Networks • Measurement and P2P Traffic Characteristics • Advanced P2P Computing and Networking This comprehensive volume serves as an essential reference for researchers and professionals, The book is also suitable for computer science and engineering students at the advanced undergraduate level or higher who are familiar with networking, network protocol concepts, and basic ideas about algorithms.